Investigating the Impact of Special Education Policies on the Psychological Well-Being of Exceptional Students - Peixoto, Beatriz; Arefi, Mozhgan; Mata, Giselle (Psychological Research in Individuals with Exceptional Needs, 2025)
This study aimed to explore the impact of special education policies on the psychological well-being of exceptional students. This qualitative research employed a phenomenological approach, utilizing semi-structured interviews with 33 exceptional students recruited through online platforms. The study relied on theoretical saturation to determine the final sample size. Data were analyzed using thematic analysis with the support of NVivo software, following an inductive coding process to identify key themes related to emotional and psychological well-being, policy implementation, and future prospects of exceptional students. The results revealed three primary themes: emotional and psychological impacts, the effectiveness of special education policies, and long-term student outcomes. Participants reported experiences of stigmatization, social exclusion, and policy-related stress, which significantly affected their emotional well-being. While some students benefited from individualized education plans and supportive teacher interactions, others faced inconsistencies in policy implementation, leading to increased anxiety and uncertainty. The study also highlighted the crucial role of parental advocacy and teacher preparedness in ensuring the effectiveness of special education policies. Long-term concerns included access to higher education, career readiness, and independent living skills, with many participants expressing uncertainty about future accommodations and opportunities. The study underscores the critical influence of special education policies on the psychological well-being of exceptional students, emphasizing the need for stable, well-implemented policies, improved teacher training, and stronger parental engagement. Addressing inconsistencies in policy application and enhancing emotional support mechanisms within educational settings are essential steps toward fostering the well-being and long-term success of exceptional students.